Analysis of Understanding Education Digitization Concept during the Pandemic in North Sulawesi Province - Lady Grace Jane Giroth,; Jeffry Sony Junus Lengkong,; Viktory Nicodemus Joufree Rotty, (Technium Social Sciences Journal, 2023)
This study intends to ascertain how private university lecturers in North Sulawesi understand digitalization in order to enhance their performance. The performance of private university professors will improve with knowledge of the servant leadership philosophy. This study focused on North Sulawesi-based private university lecturers. Purposive sampling is used to support the descriptive research methodology. In this study, the participants were professors at private universities in North Sulawesi. Thirty PTS lecturers in North Sulawesi who were known to be PTS teachers had their samples collected. The findings demonstrated a favourable correlation between lecturers' participation and their comprehension of digitalization in education. However, the lack of PTS leaders' involvement in providing their staff with opportunities for growth, encouragement, trust, and service undermines their potential, sense of pride, and capacity to uphold the tridharma of higher education. The organisational culture's value alignment does not promote the best teaching, volunteerism, or research in fields like community pride. Lack of leadership and a culture that supports the role of self-efficacy and work spirituality as performance intervenors are the root causes of the failure to carry out education and teaching, research, and community service.